Establishing hematological reference intervals in healthy adults: Ravansar non‐communicable disease cohort study, Iran. (23rd October 2020) - Moradinazar, Mehdi; Najafi, Farid; Pasdar, Yahya; Hamzeh, Behrooz; Shakiba, Ebrahim; Bohn, Mary Kathryn; Adeli, Khosrow; Rahimi, Zohreh
Abstract: Introduction: It is necessary to establish hematological reference intervals (RIs) in each population to improve disease management and healthcare quality. This study aimed to establish age‐ and sex‐specific hematological RIs in a healthy adult Kurdish population and evaluate the influence of select lifestyle factors. Methods: Hematological parameters were studied in 6518 individuals (3006 females, 3512 males) from Ravansar Non‐Communicable Disease (RaNCD) cohort study. Hematological parameters were measured by Beckman Coulter HmX Analyzer. After combined application of exclusion criteria and statistical outlier removal, RIs for all partitions were calculated using nonparametric methods. Results: The present study established hematological RIs for 14 parameters in a healthy adult Iranian population. Reference values for some analytes demonstrated significant age‐ and sex‐specific differences and were slightly different when compared to RIs determined in other populations. Furthermore, the current smokers had higher levels of white blood cells (WBCs), red blood cells (RBCs), hemoglobin, hematocrit, mean corpuscular hemoglobin (MCH), and mean corpuscular volume than ex‐ and nonsmokers. Also, in the presence of high physical activity, elevated levels of RBC, hemoglobin, hematocrit, monocytes, and MCH were observed, as well as lower WBC levels. Further, a significant positive association was observed between body mass index (BMI) and WBC, red cell distribution width, and plateletcrit levels. Conclusion: Our study suggests hematological parameters are influenced by age, sex, and lifestyle factors such as physical activity and BMI. Additionally, discrepancies when compared to other population studies suggest that ethnic‐specific differences need to be considered when establishing RIs for hematological parameters.